High responsivity, self-powered carbon–zinc oxide hybrid thin film based photodetector - Ahmad, Harith; Thandavan, Tamil Many K. (Springer Verlag, 2018)
A self-powered n-Si/C–ZnO/SiO2/p-Si heterojunction photodetector (PD) which comprises of carbon (C) and zinc oxide (ZnO) nanostructures on a n-type silicon (n-Si) substrate was prepared via vapor phase transport method. Excellent photodetection under 468 nm light illumination for powers ranging from 2.78 to 2910 µW delivered a quick response of about 9.5 µs. A high photoresponsivity of 2.082/AW and external quantum efficiency about 551% were obtained. The mechanism involved for the generation of a photocurrent at a zero bias voltage was discussed for future energy efficient optoelectronics devices. The morphology and composition of C, Zn and O were confirmed by field emission scanning electron microscope, energy dispersive X-ray and Raman scattering analysis. The formation of ZnO nanowires range from 10 to 100 nm, aided by the photoconduction mechanism. The Raman E2 high mode of 437/cm of ZnO and the presence of D and G bands show the formation of a hybrid C–ZnO thin film. The calculated rectifying ratio is found to shift as the direct current bias voltage and light power increased. The deposition of C particles on the ZnO surface creates point defects and sub-energy levels in the ZnO bandgap which favour fast responsivity in the PD.